Electrical Conductivity Variation With Temperature of Irradiated Standard Malaysian Rubber(SMR) - Sanaa Al-Delaimy (College of Education for Pure Sciences, 2005)
Electrical conductivity variation with temperature in the range (303-368)K during heating and cooling has been studied for irradiated SMR material using Alpha and Beta - particles and Gammarays . It was found that the values of conductivity during cooling are higher than that during heating for all samples before and after irradiation. Also it appears that the molecules suffer from crosslinking during irradiation with Alpha-particles , while they suffer fi·om degradation and cross-linking during irradiating with Beta-particles and Gamma-rays, depending on the irradiating time.